Nano/Micro Biotechnology - Endo, Isao; Nagamune, Teruyuki (Advances in Biochemical Engineering/Biotechnology, 2010)
Part I The Nano-Scale Biological Systems in Nature; Molecular bio-motors in living cells - by T. Nishizaka; The form designed by viral genome - by K. Onodera; Part II Detection and Characterization Technology; Atomic force microscopy applied to nano-mechanics of the cell - by A. Ikai; Design, synthesis and biological application of fluorescent sensor molecules for cellular imaging - by K. Kikuchi; Dynamic visualization of cellular signaling - by Q. Ni and J. Zhang; Part III Fabrication Technology; Surface acoustic wave atomizer and electrostatic deposition - by Y. Yamagata; Electrospray deposition of biomolecules by V.N. Morozov; Part IV Processing Technology; Droplet handling - by T.Torii; Integrated microfluidic systems - by S. Kaneda and T. Fujii; Part V Applications; A novel non-viral gene delivery system: Multifunctional envelope-type nano device - by H. Hatakeyama, H. Akita, K. Kogure, and H. Harashima; Biosensors - by M. Saito, H.M. Hiep, N. Nagatani, and E.Tamiya; Micro bioreactors - by Sato and T. Kitamori.